Link Protein N-Terminal Peptide as a Potential Stimulating Factor for Stem Cell-Based Cartilage Regeneration - Ruijun He; Baichuan Wang; Min Cui; Zekang Xiong; Hui Lin; Lei Zhao; Zhiliang Li; Zhe Wang; Shaun Peggrem; Zhidao Xia; Zengwu Shao (Hindawi Limited, 2018)
Background. Link protein N-terminal peptide (LPP) in extracellular matrix (ECM) of cartilage could induce synthesis of proteoglycans and collagen type II in cartilaginous cells. Cartilage stem/progenitor cells (CSPCs), the endogenous stem cells in cartilage, are important in cartilage degeneration and regeneration. We hypothesized that LPP could be a stimulator for stem cell-based cartilage regeneration by affecting biological behaviors of CSPC. Methods. CSPCs were isolated from rat knee cartilage. We evaluated the promoting effect of LPP on proliferation, migration, and chondrogenic differentiation of CSPCs. The chondrogenic differentiation-related genes and proteins were quantitated. Three-dimensional culture of CSPC was conducted in the presence of TGF-β3 or LPP, and the harvested pellets were analyzed to assess the function of LPP on cartilage regeneration. Results. LPP stimulated the proliferation of CSPC and accelerated the site-directional migration. Higher expression of SOX9, collagen II, and aggrecan were demonstrated in CSPCs treated with LPP. The pellets treated with LPP showed more distinct characteristics of chondroid differentiation than those with TGF-β3. Conclusion. LPP showed application prospect in cartilage regeneration medicine by stimulating proliferation, migration, and chondrogenic differentiation of cartilage stem/progenitor cells.